Comparison of Gait Symmetry and Joint Moments in Unilateral and Bilateral Hip Osteoarthritis Patients and Healthy Controls - van Drongelen, S.; Braun, S.; Stief, F.; Meurer, A. (Frontiers in Bioengineering and Biotechnology, 2021)
Patients with unilateral hip osteoarthritis show a characteristic gait pattern in which they unload the affected leg and overload the unaffected leg. Information on the gait characteristics of patients with bilateral hip osteoarthritis are very limited. The main purposes of this study were to investigate whether the gait pattern of both legs of patients with bilateral hip osteoarthritis deviates from healthy controls and whether bilateral hip osteoarthritis patients show a more symmetrical joint load compared to unilateral hip osteoarthritis patients. In this prospective study, 26 patients with bilateral hip osteoarthritis, 26 patients with unilateral hip osteoarthritis and 26 healthy controls were included. The three groups were matched for gender, age and walking speed. Patients were scheduled for a unilateral total hip arthroplasty on the more affected/more painful side. All participants underwent a three-dimensional gait analysis. Gait kinematics and gait kinetics of patients and controls were compared using Statistical Parametric Mapping. Corrected for speed, the gait kinematics and kinetics of both legs of patients with bilateral hip osteoarthritis differed from healthy controls. Bilateral patients had symmetrical knee joint loading, in contrast to the asymmetrical knee joint loading in unilateral hip osteoarthritis patients. The ipsilateral leg of the bilateral patients could be included in studies in addition to unilateral hip osteoarthritis patients as no differences were found. Although patients with bilateral hip osteoarthritis show more symmetrical frontal plane knee joint moments, a pathological external knee adduction moment in the second half of stance was present in the ipsilateral leg in patients with unilateral and bilateral hip osteoarthritis. The lateral adjustment of the knee adduction moment may initiate or accelerate progression of degenerative changes in the lateral compartment of the knee.